Brahmi - A Promising Medicinal Herb - Sridhar, Rathod; Sarkar, Narayan Chandra (Chronicle of Bioresource Management, 2021)
Brahmi (Bacopa monnieri) has been used for centuries for a variety of purposes, including improving memory, alleviate anxiety and stress, treating epilepsy etc., It contains a principal chemical bacosides responsible for all these medicinal properties. The antioxidants protect against cell damage caused by potentially harmful molecules and fight against chronic diseases like heart disease, diabetes and certain cancers, attention deficit hyperactivity disorder (ADHD)- a neuro-disorder characterized by hyperactivity, impulsivity and inattentiveness. The plant can be grown in a wide variety of soils, but prefers soil with high water holding capacity. It has the ability to thrive in wet environment and soils rich in organic matter. Unlike cash crops, this plant can give potential yield with minimal agronomic management thus found remunerative.